ANATOMY AND IDENTIFICATION OF CHARCOAL MARKETED IN THE REGION OF PAPANDUVA, SANTA CATARINA, SOUTHERN BRAZIL. - Gmach, Franciele; Cubas, Rafael; Ribeiro Morrone, Simone; Nisgoski, Silvana (Floresta, 2023)
The objective of this paper was identifed anatomically and describe wood species marketed as charcoal in the region of Papanduva, SC, southern Brazil, to provide technical information to help in identification of species from the Atlantic Forest biome. Packages of 3 to 10 kg of charcoal were purchased, a pre-selection from more similar pieces was performed, macro and microscopic images were obtained for posterior anatomical description and material identification. Mislabeling was found in some charcoal packages, including genus, from both angiosperm and gymnosperm groups. Samples were found in decreasing frequency order, from the genera Eucalyptus/Corymbia, Ocotea/Nectandra, Acacia, Pinus, Araucaria, Alchornea, Casearia, Cedrela, Eugenia, Hieronyma, Ilex, Schinus and Zanthoxyllum. In gymnosperms, it was possible to verify growth rings distinct, with differences in cell wall thickness of tracheid and resin canals in pinus. In angiosperms, diffuse porosity was more frequent, with highlight to semiring porous in genus Cedrela. The presence of tyloses was predominant in genus Eucalyptus/Corymbia; septate fibers were characteristics for genus Ocotea/Nectandra. Simple perforate plate and alternate intervessel pits were predominant, with exception of genus Ilex with scalariform perforation plate and opposite intervessel pits. Secretory canals were observed in genus Zanthoxyllum. The predominance of eucalyptus from planted forests was observed, but the presence of araucaria, which is on the list of endangered species, indicated the importance of better supervision and training for awareness of producers and local traders.